Analytic-behavioral therapy for women with anxiety and depression: behaviors and procedures in the therapeutic interaction - Levatti, Giovanna Eleutério; Victuri, Alexandre Aguiar; Garcia, Vagner Angelo; Bolsoni-Silva, Alessandra Turini (Perspectivas em Análise do Comportamento, 2019)
Anxiety and depression disorders present high prevalence in women. The present article describes behaviors and behavioral analytical intervention procedures in single case delineation. The participants were two women with clinical symptoms of anxiety and depression, who responded to social skills and mental health instruments in four moments (pre-test, intermediate, post-test and follow-up). After the intervention and in the follow-up, the symptoms of anxiety and depression became non-clinical, and there was acquisition of social skills during the process. Regarding the therapeutic interaction, the highlights were the behaviors facilitation, report request, reflection request and approval by the therapists, and the behaviors report, relation establishment, improvement and self-knowledge/self-control by the clients. The most frequent intervention procedures were functional analysis and differential reinforcement. The results pointed out that the occurrence of some behaviors, themes and procedures did not vary between the therapist-client dyads, which indicates a certain stability of the behavioral approach for since it can indicate the constancy of the management used for the participants of this study. The study allowed us to describe behavior and intervention procedures with evidence of improvement in the problems presented previously.